Constitutional basis of the adversarial criminal justicesystem in a social State of law - Araque de Navas, Cándida Rosa (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This scenario is suitable to consider some aspects related to the constitutionalization of criminal law as a categorical expression of a genuine democratic State of law focused on human dignity, with the subsequent humanization of justice administration. The Constitution of 1991 should be applied preferably in judicial activity. It implies that this norm went from being formal to material source of law, i.e., that decisions to be taken in any kind of judgment or procedures should consider the Constitution -understood composed of the so-called Constitutional Bloc-, because so ordains its article 4: “The Constitution is the supreme law and prevails over any other provisions contrary to it”. It is precisely this situation that led to a new constitutional criminal reading: rights and guarantees on top of adversarial principle and international law of human rights.